Patient Preference for Optical Coherence Tomography versus Punch Biopsy as Diagnostic Strategy for Diagnosis of Basal Cell Carcinoma: A Labelled Discrete Choice Experiment - Fieke Adan; Klara Mosterd; Tom Wolswijk; Nicole W.J. Kelleners-Smeets; Brigitte A.B. Essers (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)